Why misinformation is reported: evidence from a warning and a source-monitoring task. Issue 10 (25th November 2016) - Wyler, Helen; Oswald, Margit E.
ABSTRACT: People report suggested misinformation about a previously witnessed event for manifold reasons, such as social pressure, lack of memory of the original aspect, or a firm belief to remember the misinformation from the witnessed event. In our experiments ( N  = 429), which follow Loftus's paradigm, we tried to disentangle the reasons for reporting a central and a peripheral piece of misinformation in a recognition task by examining (a) the impact a warning about possible misinformation has on the error rate, and (b) whether once reported misinformation was actually attributed to the witnessed event in a later source-monitoring (SM) task. Overall, a misinformation effect was found for both items. The warning strongly reduced the misinformation effect, but only for the central item. In contrast, reports of the peripheral misinformation were correctly attributed to the misinformation source or, at least, ascribed to guesswork much more often than the central ones. As a consequence, after the SM task, the initially higher error rate for the peripheral item was even lower than that of the central item. Results convincingly show that the reasons for reporting misinformation, and correspondingly also the potential to avoid them in legal settings, depend on the centrality of the misinformation.